A Window into Public Education: Documenting Neoliberal Capitalism’s Harms, Advocating for Alternatives - Parker, Lana (Critical Education)

(untitled) (Institute for Critical Education Studies / UBC, 2025)
Decades of neoliberal capitalism have had a corrosive effect on public education, with implications for both the fiscal realities of education systems and the ideological values guiding curriculum and pedagogy. While the culture of neoliberalism has often been studied, it is equally important to expand analyses of the shifting material conditions of how capital moves through education systems, reshapes power, and exacerbates inequality. It is also, I argue, vitally important to document—to be mindful—of how the affordances of the present, once eroded, diminish the imaginings of what is possible in the future. To that end, in this special issue, we highlight the twin realities of neoliberalism. We also make the argument for public education, imperfect though its current iterations may be, as a valuable inheritance of public good.